Discourses on childhoods in university Physical Education Teacher training (1964-1983) (Praxis Educativa, 2023)
In the present article we analyze the place, the notions and the discourses about childhoods in the University Teacher Training of Physical Education of the National University of La Plata during the period 1964 to 1983. In a first moment, we inquired into the structural-formal aspects of the curriculum of the subject Physical Education for children based on the aspects of the place and the sense given to childhood. In turn, we confronted such analysis with an interview with the teacher in charge of the subject to learn about the discourses about childhoods present in professional training. In this sense, we were able to identify the conformation and consolidation of diverse discursive matrices regarding the children's world: childhoods as an object of concern for Physical Education and its teacher training and rhetorics about the universalization of childhoods.
Keywords: Physical Education; childhood; speeches; teacher training; curriculum